Arabic Neologisms in Indonesian and Malaysian Arabic Media - Sukiman, Uki; Zainuddin, Ghazali; Yoyo, Yoyo; Ramlan, Siti Rosilawati (Al-Jami'ah Research Centre, 2023)
This research examines new, unique Arabic terms and vocabulary used in the newspapers Indonesia Alyoum and Aswaq, two online media based in Indonesia and Malaysia, respectively, to elaborate on the development of the Arabic language in non-Arab countries. The invention of new Arabic words in these media primarily used the methods of al-taulīd bi al-iqtirāḍ, particularly al-dakhīl, and al-taulīd al-dalālī using al-tarjamah al-ḥarfiyah. Meanwhile, the method al-taulīd bi al-majāz, a metaphorical method, is to invent new, unique, local terms. However, the authors argue that both newspapers have differences in transliteration and inconsistent use of terms. In response to this language development, Malay Muslims show their potential to develop Malay-Arabic transliteration guidelines, compile a new Arabic dictionary, and even establish Southeast Asian Majma‘ al-Lugah al-‘Arabiyah. [Penelitian ini mengkaji istilah-istilah dan kosakata baru dan unik dalam bahasa Arab yang digunakan di surat kabar Indonesia Alyoum dan Aswaq, dua media online yang masing-masing berbasis di Indonesia dan Malaysia, untuk melihat perkembangan bahasa Arab di negara non-Arab. Pembentukan kosa kata baru pada media ini terutama menggunakan metode al-taulīd bi al-iqtirāḍ, khususnya al-dakhīl, dan al-taulīd al-dalālī yang berbasis al-tarjamah al-ḥarfiyah. Sedangkan metode al-taulīd bi al-majāz, metode metafora, dipakai untuk mengalihkan istilah-istilah lokal. Namun, kedua surat kabar tersebut memiliki perbedaan dalam transliterasi dan tidak konsisten dalam penggunaan kosa kata serapan tersebut. Sementara itu, dalam menyikapi perkembangan bahasa Arab ini, umat Islam Melayu berpotensi mengembangkan pedoman transliterasi Melayu-Arab, menyusun kamus bahasa Arab baru, bahkan mendirikan Majma‘ al-Lugah al-‘Arabiyah Asia Tenggara.]